Effect of Bentonite Fining on Proteins and Phenolic Composition of Chardonnay and Sauvignon Blanc Wines - He, Shan; Hider, Richard; Zhao, Jenny; Tian, Bin (South African Journal of Enology and Viticulture, 2020)
Bentonite fining is widely used to remove excess proteins in white wine prior to bottling in order to prevent protein haze formation. However, bentonite fining could also remove beneficial compounds in wine, e.g. phenolic compounds that contribute to sensory properties of wine. In this study, impact of bentonite fining on the phenolic composition of Chardonnay and Sauvignon Blanc wines has been investigated using four different bentonites: pluxcompact (PCT, Ca bentonite); bentolit (BTL, Na-Ca bentonite); pluxbenton (PBN, Na bentonite); and sperimentale (SPM, Ca-Na bentonite). Different bentonites showed similar efficiencies in removing haze-related proteins and resulted in significant decrease in total phenolic concentration. Impact on phenolic composition varied depending on the type of bentonite. In this study, fining with Ca-Na bentonite (SPM) resulted in the lowest concentrations of caftaric acid and flavanols, particularly epicatechin gallate, gallocatechin, catechin and epicatechin, which could lead to reduced mouthfeel of the resultant wine. Results presented in this study provided additional information for winemakers to choose appropriate bentonite to remove proteins with a minimal effect on reduction of phenolic compounds.